Preferences for Reforms : Endowments vs. Beliefs - Duval, Romain (IMF Working Papers; Working Paper ;, 2022)
Are preferences for reforms driven by individuals' own endowments or beliefs? To address this question, we conducted a cross-country survey on people's opinions on employment protection legislation-an area where reform has proven to be difficult and personal interests are at stake. We find that individuals' beliefs matter more than their own endowments and personal pay-offs. A randomized information treatment confirms that beliefs explain views about reform, but beliefs can change with new information. Our results are robust to several robustness tests, including to alternative estimation techniques and samples.